The effect of nitrogen content in organic fertilizer on nutrient content of sorghum hydroponic fooder - Poespitasari Hazanah Ndaru; Asri Nurul Huda; Mashudi Mashudi; Marjuki Marjuki (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2021)
The hydroponic method could be used as a solution to overcome the difficulty of the availability and continuity of fodder. One of the fodder that can be developed using hydroponic method is sorghum. The purpose of this study was to evaluate the quality of hydroponic sorghum fodder as a feed alternative for ruminants. The treatment used in this study was the use of organic fertilizer as a nitrogen source which was derived from cow and goat manures. The treatments used in this study were P0: 36 ml EM4 + molasses, P1: 36 ml EM4 + molasses + cattle manure, and P2: 36 ml EM4 + molasses + goat manure. Each treatment consisted of 40 g of sorghum seeds. The fodder was harvested at 7, 14 and 21 days of age. The variables observed of this study were nutrient content, in vitro digestibility value, and gas production. Based on the results of the study, it could be concluded that the use of EM4 + molasses + cattle manure as a fertilizer provides the most optimum nutrient content, in vitro digestibility, and gas production of hydroponic sorghum fodder.